Low-dose immunogenic chemotherapeutics promotes immune checkpoint blockade in microsatellite stability colon cancer - Fang, Yuhang; Sun, Haoyu; Xiao, Xinghui; Tang, Maoxing; Tian, Zhigang; Wei, Haiming; Sun, Rui; Zheng, Xiaodong (Frontiers in Immunology, 2022)
More than 85% of colorectal cancer (CRC) patients, who are with microsatellite stability (MSS), are resistant to immune checkpoint blockade (ICB) treatment. To overcome this resistance, combination therapy with chemotherapy is the most common choice. However, many CRC patients do not benefit more from combination therapy than chemotherapy alone. We hypothesize that severe immunosuppression, caused by chemotherapy administered at the maximum tolerated dose, antagonizes the ICB treatment. In this study, we found that low-dose oxaliplatin (OX), an immunogenic cell death (ICD)-induced drug, increased the antitumor response of TIGIT blockade against CT26 tumor, which is regarded as a MSS tumor. Combined treatment with OX and TIGIT blockade fostered CD8+ T-cell infiltration into tumors and delayed tumor progression. Importantly, only low-dose immunogenic chemotherapeutics successfully sensitized CT26 tumors to TIGIT blockade. In contrast, full-dose OX induces severe immunosuppression and impaired the efficacy of combination therapy. Further, we also found that lack of synergy between nonimmunogenic chemotherapeutics and TIGIT blockade. Consequently, this study suggests that the strategies of combination treatment of chemotherapy and ICB should be re-evaluated. The chemotherapeutics should be chosen for the potential to ICD and the dosage and regimen should be also optimized.